2017
DOI: 10.1021/acs.est.7b05520
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Bioavailability of Pyrene Associated with Dissolved Organic Matter of Various Molecular Weights to Daphnia magna

Abstract: Dissolved organic matter (DOM) is a key environmental factor for the bioavailability of hydrophobic organic compounds (HOCs) in natural waters. However, the bioavailability of DOM-associated HOCs is not clear. In this research, pyrene was selected as a model HOC, and its freely dissolved concentration (C) was maintained by passive dosing systems. The immobilization and pyrene content in the tissues excluding gut of Daphnia magna were examined to quantify the bioavailability of DOM-associated pyrene. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 59 publications
6
29
0
Order By: Relevance
“…Their hydrophobicity has generated a lot of concerns amongst the general public because of the accompanying risks to humans, environment, and aquatic organisms. They associate freely with dissolved organic matter in the natural water through several means of binding and adsorption, especially those with high molecular weights (Akkanen et al 2005 ; Zheng et al 2007 ; Smith et al 2011 ; Yu et al 2011 ; Lin et al 2018 ) and are subsequently deposited in the sediment, thus accumulating to a higher level of toxicity in the aquatic environment (Prabhukumar and Pagilla 2010 ; Brazkova and Krastanov 2013 ; Olatunji et al 2014 ). The bioavailability of PAHs to the aquatic animals and also their penetration of dietary sources has thus become unavoidable (Sakuma et al 2011 ; Adeniji et al 2018b ).…”
mentioning
confidence: 99%
“…Their hydrophobicity has generated a lot of concerns amongst the general public because of the accompanying risks to humans, environment, and aquatic organisms. They associate freely with dissolved organic matter in the natural water through several means of binding and adsorption, especially those with high molecular weights (Akkanen et al 2005 ; Zheng et al 2007 ; Smith et al 2011 ; Yu et al 2011 ; Lin et al 2018 ) and are subsequently deposited in the sediment, thus accumulating to a higher level of toxicity in the aquatic environment (Prabhukumar and Pagilla 2010 ; Brazkova and Krastanov 2013 ; Olatunji et al 2014 ). The bioavailability of PAHs to the aquatic animals and also their penetration of dietary sources has thus become unavoidable (Sakuma et al 2011 ; Adeniji et al 2018b ).…”
mentioning
confidence: 99%
“…Therefore, it should also be considered that DOM may have reduced the freely dissolved concentration of TPhP to an extent where a different metabolic response was seen with TPhP and DOM exposure compared to TPhP only exposure [ 8 ]. DOM may have enhanced the bioavailability of TPhP to D. magna [ 11 ]. A previous study conducted over 48 h with pyrene (60 µg/L) in the presence of 30 mg DOC/L found that the bioaccumulation of pyrene in D. magna increased by 42–92% compared to controls without DOM [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…DOM may have enhanced the bioavailability of TPhP to D. magna [ 11 ]. A previous study conducted over 48 h with pyrene (60 µg/L) in the presence of 30 mg DOC/L found that the bioaccumulation of pyrene in D. magna increased by 42–92% compared to controls without DOM [ 11 ]. In addition, it was reported that DOM can enhance the water solubility of some hydrophobic organic contaminants likely due to a partitioning interaction with DOM, which may contribute to the increased uptake of organic contaminants in aquatic organisms [ 11 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations